Adhesion of underwater repair concrete to vertical surfaces - Elżbieta Horszczaruk; Piotr Brzozowski (Case Studies in Construction Materials, 2025)
The paper presents the results of testing the influence of hydrostatic pressure and the method of surface preparation on the adhesion of repair concrete to the vertical substrate. A specially designed and constructed steel container (a chamber) has been used to place the repair concrete underwater and cure it under hydrostatic pressure. A frame installed on the container’s bottom enabled the concrete substrate to be placed, simulating the vertical wall of the structure. The concrete substrate’s surface, on which the repair concrete was placed, has been initially treated by hammering and sand-blasting. The SRI index characterised the degree of surface treatment. The prepared substrates with placed repair concrete underwent hydrostatic pressure from 0.1 to 0.5 MPa for 28 days. After curing, the adhesion of the repair concrete to the substrate was determined using the pull-off method. Based on the results obtained, the effect of hydrostatic pressure and substrate preparation on the adhesion of the repair concrete to the vertical surfaces was analysed. The location of the tested samples in the repaired element (the distance of the sample to the upper edge of the element) has been considered. An apparent influence of the hydrostatic pressure on the concrete’s adhesion has been found in the case of the sand-blasted substrate. However, no significant effect of the hydrostatic pressure was observed for the hammered surface.